Detection and genetic characterization of novel infectious bronchitis viruses from recent outbreaks in broiler and layer chicken flocks in southern China, 2021 - Sheng Yuan; Qing Cheng; Jinyue Guo; Zhili Li; Jing Yang; Congying Wang; Zhipeng Liang; Xinyu Zhang; Hai Yu; Yong Li; Shujian Huang; Feng Wen (Poultry Science, 2022)
Avian infectious bronchitis virus (IBV) is a prevalent RNA virus that causes respiratory distress, nephritis, salpingitis, and egg production decline in chickens, resulting in significant economic loss. IBV is composed of complex genotypes and serotypes, which poses a great challenge for disease control. The current study reports 2 IBV outbreaks which were characterized by respiratory symptoms in IBV vaccinated commercial broilers and layers in Guangdong, China, in 2021. Two IBV strains, ZH01 and HH09, were identified via a RT-PCR assay through targeting the N gene and further characterization through full-length spike (S) gene sequence analysis. Phylogenetic analysis of S1 gene revealed that both ZH01 and HH09 belonged to the GI-19 lineage but contained a certain genetic distance from the GI-19 strain. Of note, the ZH01 and HH09 strains share a low homology of 70 and 86%, respectively, with common vaccine strains (H120), resulting in low vaccine protection. Further recombination analysis based on the S1 sequence suggested the newly identified IBV strains emerged through an intragroup recombination events between CK/CH/SCDY2003-2 and I0305/19 from G1-19 lineage. In addition, a number of novel mutations such as T273I, T292A, and S331K were found in the emerging IBV strains. Taken together, this study reports the genetic characteristics of 2 recent IBV outbreaks in southern China and emphasizes the urgent need for enhanced surveillance and development of novel vaccines for the control of IBV.